Penerapan Sanksi Pidana Kepada Anak Dibawah Umur Pemakai Narkotika (Studi Pada Polrestabes Medan) - Dimas Adit Sutono; Alpi Sahari; Surya Perdana (Journal Recht (JR), 2022)
Drug abuse is no longer a victimless crime but is already a crime that takes many victims and a prolonged disaster. Drug abuse in Indonesia is increasingly showing concern because many people who are not for health reasons are suspected of actively using narcotics. The research method in this study using the normative approach. i.e. conducts library research by researching and collecting library materials specifically relating to laws and regulations and books relating to law and narcotics, as well as field research conducted by observations observations and direct interviews with related objects. The results of this study show that: first, the legal regulation on drugs Law No. 35 of 2009 concerning Narcotics. Efforts to protect children's law are governed by various laws and regulations. Second, the factors causing the occurrence of criminal acts of drug abuse by children are caused by: age factors, wrong views, lack of religion in the child, family, economy, and environmental factors. Enforcing the law for children who commit narcotics drug offenses, the Polrestabes is striving for preventive and repressive measures, the police in Medan have also cooperated in conducting investigations into cases of drug abuse by children. Third, the role of Medan Polrestabes in eradicating drug crimes is carried out, namely; by way of countermeasures by reasoning (criminal law) and efforts to counteract secaranon penal.